Energy-Efficient Cloud Computing: A Survey - Mohammed Marzook Fathima Fahima; Abul Hassan Sahna Sreen; Sinna Lebbe Fathima Ruksana; Mohamed Hasan Mohamed Majid (Penerbit Hellow Pustaka, 2025)
This comprehensive assessment examines the rising energy usage and environmental risks linked with the rapid growth of cloud computing. It investigates a variety of technologies and tactics targeted at enhancing cloud computing's energy efficiency and sustainability. The research looks at the complexities of cloud computing, examining how diverse applications, workloads, and server designs affect performance and energy consumption. It emphasizes virtualization and consolidation as major strategies for optimizing energy utilization. The notion of